Anatomia de la madera de 9 especies del genero Cordia L. (Boraginaceae-Cordioideae) que crecen en Venezuela - Leon H, W.J.
(En, Es)
ilus., 27 ref
Keywords: CORDIA; BORAGINACEAE; ANATOMIA DE LA MADERA; XILEMA; VENEZUELA